Spatial Analysis of E-Warong Distribution for Basic Food Social Assistance Program in Surakarta City - Dewi Novita Sari; Sitti Retno Faridatussalam; Moh. Ali Ma’sum; Hasna Afif Labiba (Politeknik Negeri Batam, 2023)
The social assistance for the basic food program launched by the Indonesian Ministry of Social Affairs in 2020 seeks social protection for Family Beneficiaries (KPM/Keluarga Peneri-ma Manfaat). One of the distribution constraints is the absence of a database and spatial analysis for the distribution process of social assistance for basic food programs. This study aimed to inventory data on the location of e-warong, visualize, and analyze distance coverage. The method included a survey of the coordinates of the e-Warong location and an analysis of secondary data from the Surakarta City Social Service (Dinas Sosial Kota Surakarta) for March 2022. The data was processed using proximity analysis on Geographic Information System (GIS)-based software to map the affordability of e- Warong services. The results obtained are the creation of a database of e-Warong locations, mapping of accessibility, and the range of e-Warong services to KPM. The accessibility map of the e-warong location is 100 m for the near zone (most covered), 300 m for the medium zone (covered), and 500 m for the far zone (poorly covered). In conclusion, the e-warong service area is partially centered between Pasar Kliwon and Banjarsari. Meanwhile, several locations in Jebres, Serengan, and Laweyan are still unreachable.